APPRAISAL OF RESEARCH METHODOGY COURSE FOR UNDERGRADUATE EDUCATION STUDENTS: IMPLICATIONS FOR CURRICULUM DEVELOPMENT - P.N. Okorji; V.N. Nwogbo (European Scientific Journal, ESJ, 2014)
The purpose of this research was to appraise the adequacy of the preparatory methodology course in terms of meeting the needs of the students for whom the course was designed. In conducting the study, five research questions based on the needs of the students guided the research work. All the 276 students who took the course in the Faculty of Education in 2012/2013 were used for the study. A- 36 item questionnaire was used to collect data from the students. The mean, mode, standard deviation were used to analyzed and answer the questions raised in the study. The findings among others revealed that out of the nine units of Research Methodology course, only three, namely Introduction to Education Research Population and Description, Research Questions and Hypothesis are adequate in meeting student’s needs. Aspects of the course like problem identification, literature review, designs and statistical analysis require modification, in other to meet the needs of the students for whom the course was designed for. However, based on these findings some recommendations were made.